Valley fever under a changing climate in the United States - Madelynn H. Howard; Christie M. Sayes; John P. Giesy; Yang Li (Environment International)
This review summarizes studies on the relationships between climate change and Valley Fever (VF), also termed Coccidioidomycosis, a potentially fatal upper-respiratory fungal infection caused by the pathogenic fungi, C. immitis or C. posadasii. The intensified onset of climate change has caused frequencies and possibly intensities of natural hazard events like dust storms and drought to increase, which has been correlated with greater prevalence of VF. These events, followed by changes in patterns of precipitation, not only pick up dust and spread it throughout the air, but also boost the growth and spread of Coccidioides. In California alone, cases of VF have increased fivefold from 2001 to 2021, and are expected to continue to increase. From 1999 to 2019, there was an average of 200 deaths per year caused by VF in the United States. The number of deaths caused by VF fluctuates year to year, but because more infections are predicted to occur due to a changing climate, deaths are expected to rise; thus, the rising prevalence of the disease is becoming a larger focus of the scientific community and poses an increased threat to public health. By reviewing recent and past studies on Coccidioidomycosis and its relationships with climate factors, we categorize future impacts of this disease on the United States, and highlight areas that need more study. Factors affecting the incidence of VF, such as modes of dispersal and the optimum environment for Coccidioides growth, that could potentially increase its prevalence as weather patterns change are discussed and how the endemic regions could be affected are assessed. In general, regions of the United States, including California and Arizona, where VF is endemic, are expanding and incidences of VF are increasing in those areas. The surrounding southern states, including Nevada, New Mexico, Utah, and Texas, are experiencing similar changes. In addition, the entire endemic region of the United States is predicted to spread northward as drought is prolonged and temperatures steadily increase. The findings from the keyword search from eight databases indicate that more studies on VF and its relation to dust and climate are needed especially for endemic states like Nevada that are currently not adequately studied. Overall, results of this survey summarize mechanisms and climate factors that might drive spread of VF and describes trends of incidence of VF in endemic states and predicted likely trends that might occur under a changing climate. Through reviewing recent and past studies of Coccidioidomycosis and its relationships with climate factors, future impacts of this disease have been categorized and speculated on effects it might have on the United States. Better understanding of how climate factors affect VF as well as identifying regions that require more research could inform both environmental managers and medical professionals with the resources needed to make more accurate predictions, design better mitigation strategies, send timely warnings, and protect public health.Shortened versionThis review explores how climate change affects Valley Fever (VF), a dangerous fungal infection caused by C. immitis or C. posadasii. Climate change has increased natural hazard events such as dust storms and droughts, which have caused the spread of VF. Cases of the disease have increased fivefold between 2001 and 2021 in California alone, and it poses an increasing threat to public health. The review summarizes mechanisms that drive the spread of VF and highlights trends in endemic states under a changing climate. It recommends more studies on VF and its relation to dust and climate, especially for states like Nevada. Identifying regions that require more research can help make more accurate predictions, design better mitigation strategies, send timely warnings, and protect public health.